Biomarkers of endothelial activation and ATP-binding cassette transporter A1 (ABCa1) gene variants in subjects with low HDL-c concentration / Wan Nor Hanis Wan Ahmad - Wan Ahmad, Wan Nor Hanis (2015)
Soluble vascular cell adhesion molecule-1 (sVCAM-1), intercellular cell adhesion molecule 1 (sICAM-1), and E-selectin are biomarkers reflecting endothelial activation (EA), a key event in atherosclerosis. High-density lipoprotein cholesterol (HDL-c) is protective against atherosclerosis by reverse cholesterol transport (RCT) but its association with EA is not well established. ATP-binding Cassette Transporter A1 (ABCA1) is the main transport protein in RCT and its gene variants have been linked to low HDL-c concentration. Thus, this study aimed to (a) compare the concentration of biomarkers of EA between low HDL-c subjects and normal controls (NC), (b) examine the correlation and association between HDL-c and biomarkers of EA, (c) investigate whether HDL-c concentration is an independent predictor for these biomarkers, and (d) determine the genetic variants of ABCA1. A total of 207 subjects with low HDL-c and 215 age-, gender-, ethnic-, smoking-, diabetic- and blood pressure-matched NC were recruited. Fasting blood samples were collected for biomarkers of EA and DNA extraction. Targeted regions oiABCAl gene were amplified and sequenced. The detection of the SNPs were analysed using BioEdit. Subjects with low HDL-c had greater concentrations EA biomarkers compared to controls. There were significant negative correlations and association between HDL-c concentration and EA biomarkers. HDL-c was an independent predictor for sVCAM-1. DNA sequencing of ABCA1 revealed six genetic variants and two SNPs were found to be significantly different between the low HDL-c subjects and NC in both genotype and allele frequencies. In conclusion, low serum HDL-c concentration is strongly correlated and associated with enhanced status of EA which strongly supports its role in the pathogenesis of atherosclerosis. The findings of genetic variation in ABCA1 suggest that this gene may play an important role in HDL deficiency amongst Malaysians.